Neurochemical evidence for differential effects of acute and repeated oxytocin administration - Benner, Seico; Aoki, Yuta; Watanabe, Takamitsu; Endo, Nozomi; Abe, Osamu; Kuroda, Miho; Kuwabara, Hitoshi; Kawakubo, Yuki; Takao, Hidemasa; Kunimatsu, Akira; Kasai, Kiyoto; Bito, Haruhiko; et al. (Molecular psychiatry, 2021)
A discrepancy in oxytocin’s behavioral effects between acute and repeated administrations indicates distinct underlying neurobiological mechanisms. The current study employed a combination of human clinical trial and animal study to compare neurochemical changes induced by acute and repeated oxytocin administrations. Human study analyzed medial prefrontal metabolite levels by using 1 H-magnetic resonance spectroscopy, a secondary outcome in our randomized, double-blind, placebo-controlled crossover trial of 6 weeks intranasal administrations of oxytocin (48 IU/day) and placebo within-subject design in 17 psychotropic-free high-functioning men with autism spectrum disorder. Medial prefrontal transcript expression levels were analyzed in adult male C57BL/6J mice after intraperitoneal injection of oxytocin or saline either once (200 ng/100 μL/mouse, n = 12) or for 14 consecutive days (200 ng/100 μL/mouse/day, n = 16). As the results, repeated administration of oxytocin significantly decreased the medial prefrontal N -acetylaspartate (NAA; p = 0.043) and glutamate–glutamine levels (Glx; p = 0.001), unlike the acute oxytocin. The decreases were inversely and specifically associated ( r = 0.680, p = 0.004 for NAA; r = 0.491, p = 0.053 for Glx) with oxytocin-induced improvements of medial prefrontal functional MRI activity during a social judgment task not with changes during placebo administrations. In wild-type mice, we found that repeated oxytocin administration reduced medial frontal transcript expression of N -methyl- d -aspartate receptor type 2B ( p = 0.018), unlike the acute oxytocin, which instead changed the transcript expression associated with oxytocin ( p = 0.0004) and neural activity ( p = 0.0002). The present findings suggest that the unique sensitivity of the glutamatergic system to repeated oxytocin administration may explain the differential behavioral effects of oxytocin between acute and repeated administration.